Comparative analysis of the characteristics of Haplorchis taichui mitochondrial genome with Metagonimus yokogawai and its ribosomal transcription unit with H. pumilio (family Heterophyidae) - Ha, Le Thi Viet; Thi Khue, Nguyen; Quyen, Dong Van; Hoa, Le Thanh (Vietnam Journal of Biotechnology, 2021)
Minute intestinal flukes, Haplorchis taichui and H. pumilio, belong to the family Heterophyidae (Trematoda: Platyhelminthes), which have been studied very limited, especially the molecular markers of the mitochondrial genomes (mtDNA) and the ribosome transcription units (rTU or rDNA). We have obtained the complete mitochondrial genome of H. taichui and the coding part of ribosome transcription unit of H. taichui and H. pumilio of Vietnam. Nucleotide and amino acid data were compared between H. taichui and Metagonimus yokogawai for genomic/gene composition, codon usage (skew/skewness), and tandem repeat units (TRU). The complete mtDNA of H. taichui (strain Htai-QT3-VN) with the length of 15,120 bp and M. yokogawai (15,258 bp; Korea; KC330755) contains 36 genes, including 12 protein-coding genes (cox1, cox2, cox3, nad1, nad2, nad3, nad4L, nad4, nad5, nad6, atp6 and cob), 2 ribosomal RNA genes (rRNA); 22 transfer RNA (tRNA or trn) and a noncoding region (NCR) between trnE and trnG, divided into 2 sub-regions containing 5 TRUs (182–183 bp/TRU). H. taichui (Vietnam and Laos) uses A = 19.56%, T = 39.71%, G = 28.34%, C = 12.39% (A + T is 59.27% ​​and G + C is 40.73%) for mtDNA construction, whose skew/skewness value at A+T is negative (–0,340) and G+C is positive (0.392); for 12 protein-coding genes (PCGs) is similar; but for the mito-ribosomal genes (MRGs, of 16S/rrnL and 12S/rrnS) it is less for A+T (57.22%) and more for G+C (42.78%). M. yokogawai had lower A+T (mtDNA/55.68%; PCGs/55.96%; MRGs/54.15%) and higher G+C usage rate than H. taichui. H. taichui of Vietnam and Laos has 10,164 bp encoding for 3,376 amino acids to construct 12 PCGs with the mostly used codons as Phenylalanine (Phe-TTT) and Leucine (Leu-TTG), and the leastly used codonsas Glutamine (Gln-CAA), Arginine (Arg-CGC). Additional condon, Thr-ACA/ACC can be added as the least used in M. yokogawai. The rTU (from 5 ’18S to 3’ 28S) of H. taichui (7,268 bp) and H. pumilio (7,416 bp) were identified with 5 genomic regions including 18S rDNA, ITS1, 5.8S rDNA, ITS2 and 28S rDNA. The 18S and 5.8S genes of both species were of the same length (1,992 bp for 18S, 160 bp for 5.8S), but different for 28S genes (3,875 bp for H. taichui and 3,870 bp for H. pumilio). ITS1 in H. taichui (797 bp) and ITS2 in H. pumilio (280 bp) do not contain TRUs, whilst ITS1 in H. pumilio (1,106 bp) contains 5 TRUs(136 bp for 3 TRU and 116 bp for 2 TRUs); and ITS2 in H. taichui (444 bp) contain 3 TRUs (83–85 bp/each).